Psychometric Properties of the Arabic Version of the Pain Resilience Scale among Lebanese Adults with Chronic Musculoskeletal Pain - Melissa Makhoul; Samar Noureddine; Huda Abu-Saad Huijer; Laila Farhood; Souha Fares; Imad Uthman; Douglas J. French; Christopher R. France (Pain Research and Management)
Background. The Pain Resilience Scale (PRS), which measures behavioral perseverance and the ability to regulate emotions and cognition despite ongoing pain, lacks an Arabic version. Objectives. This study aimed to translate, culturally adapt, and validate an Arabic version of the Pain Resilience Scale (PRS-A) among Lebanese adults. Methods. Phase 1 involved translation and cross-cultural adaptation of the PRS into Arabic. Phase 2 examined the reliability and validity of the PRS-A. A convenience sample of 154 Lebanese adults with chronic musculoskeletal pain completed the PRS-A and self-report measures of pain catastrophizing, pain self-efficacy, pain intensity and interference, depression and anxiety, and quality of life. Results. The PRS-A yielded a two-factor structure with factor 1 representing “cognitive/affective positivity” and factor 2 representing “behavioral perseverance,” accounting for 41.93% and 15.15% of the variance in pain resilience, respectively. Total PRS-A score (M = 33.20 and SD = 9.90) showed significant correlations with pain catastrophizing (M = 27.65, SD = 13.03, and r = −0.52), pain self-efficacy (median = 9.00, IQR = 4, and rho = 0.61), pain intensity (M = 4.50, SD = 2.25, and r = −0.28), pain interference (M = 4.30, SD = 2.89, and r = −0.56), physical (M = 34.95, SD = 9.52, and r = 0.34) and mental (M = 40.08, SD = 12.49, and r = 0.58) health functioning, anxiety (median = 7.00, IQR = 7, and rho = −0.57), and depression (median = 4.00, IQR = 6, and rho = −0.58). PRS-A subscale was also significantly related to all measures except pain intensity, which was correlated with cognitive/affective positivity (r = −0.33) but not behavioral perseverance (r = −0.09). Cronbach’s alpha for the PRS-A was 0.87. Conclusion. The PRS-A demonstrated validity and acceptable reliability among Arab-speaking individuals with chronic musculoskeletal pain, suggesting its potential utility for assessing pain resilience within this population.